Faktor – Faktor Yang Mempengaruhi Motivasi Para Ibu Rumah Tangga Di Kecamatan Tuah Madani Kota Pekanbaru Untuk Berwirausaha - Sukriani, Nurul; Muin, Mulyani Rody (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This study aims to determine the motivation of housewives in entrepreneurship in the District of Tuah Madani Pekanbaru by using the variables capital, independence, and education to analyze their effect on entrepreneurship motivation. The population in this study were all women who run home-based businesses in the Tuah Madani District, Pekanbaru City, whose exact number is not known, for an unknown population, the number of samples in this study used the Wibisono formula and obtained a sample of 97 people. Data collection was carried out using the questionnaire method, namely by providing a list of statements to the respondents. The data analysis technique used is multiple linear regression analysis which is operated through the SPSS 20 for Windows program. The results showed that both simultaneously and partially the variables of capital, independence, and education had a significant effect on the entrepreneurship motivation of housewives in the Tuah Madani District in Pekanbaru